2013
DOI: 10.1016/j.anr.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labour of Caring for Hematopoietic Stem Cell Transplantation Patients: Iranian Nurses' Experiences

Abstract: Iranian nurses who care for HSCT patients experience a range of positive and negative emotions. Establishing appropriate support systems for nurses might help mediate the negative aspects of emotional labour. thereby improving nursing work life and ultimately the quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…Nurses apply the strategies for supporting HSCT patients and try to reduce the risk of death by prevention, monitoring, management of dangers, following-up, continuing education program and providing spiritual care. Nurses did it by counseling, instilling hope and fading out the bitter realities as mentioned in another studies 59 .By these strategies, caring achievements were emerged 60 .…”
Section: Discussionmentioning
confidence: 91%
“…Nurses apply the strategies for supporting HSCT patients and try to reduce the risk of death by prevention, monitoring, management of dangers, following-up, continuing education program and providing spiritual care. Nurses did it by counseling, instilling hope and fading out the bitter realities as mentioned in another studies 59 .By these strategies, caring achievements were emerged 60 .…”
Section: Discussionmentioning
confidence: 91%
“…The results of previous studies showed nurses' empathic behaviors in cancer wards for cancer patients [7,63]. A recent qualitative study in caring experience of Iranian nurses showed that they developed empathic behaviors and compassion toward hematopoietic stem cell transplantation patients [64]. In Buyuk et al's study [58], there was no difference between oncology nurses' empathy in adults and pediatric wards.…”
Section: Discussionmentioning
confidence: 96%
“…Zamanzadeh, Valizadeh, Sayadi, Taleghani, Howard, and Jeddian (2013) [16] conducted a qualitative study of 18 Iraninan female nurses and argues that since women are usually more emotionally engaged than members of the opposite sex, they are likelier to be more engaged in emotional labor. The study also reported that the efforts expended by nurses in carrying out emotional labor during the course of their profession could cause them personal emotional pain, which may lead to emotional exhaustion and depression [16].…”
Section: Discussionmentioning
confidence: 99%